Gene analysis: A rare gene disease of intellectual deficiency‐Cohen syndrome. Issue 68 (24th May 2018) - Yang, Chengqing; Hou, Mei; Li, Yutang; Sun, Dianrong; Guo, Ya; Liu, Peipei; Liu, Yedan; Song, Jie; Zhang, Na; Wei, Wei; Chen, Zongbo
Abstract: Cohen syndrome is a rare, genetic, connective‐tissue disorder, which is caused by mutations in the gene COH1 (VPS13B, Vacuolar Protein Sorting 13 Homolog B) at the chromosome 8q22. The disease is rare reported, which major clinical features include postnatal microcephaly, obesity, short stature, intellectual disability, progressive retinal dystrophy, intermittent neutropenia and many other unusual facial feature. We report four patients in China who were diagnosed with Cohen syndrome by genetic testing and clinical manifestations. At the same time, we review the related literature, and further expound the molecular mechanism of the disease, a variety of clinical manifestations, treatment and prognosis.